POETICAL INTERPRETATION OF THE STRUGGLE FOR INDEPENDENCE IN 20TH CENTURY UZBEKISTAN POETRY - Minhojiddin Hojimatov (Journals Park Publishing, 2025)
By the end of the 80s of the 20th century, the awakening movement of the Uzbek intelligentsia, which had almost taken the form of a colony, began to gain strength again. This inflamed spirit began to manifest itself openly in poetry. Initially seen as a field of poetry, this field gradually turned into a field of national will in a short time. This article examines the national identity and the spirit of the struggle for freedom in the work of Uzbek poets who lived and worked during this period, as well as its poetic expression.